2017
DOI: 10.1055/s-0042-124356
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Spinal Cord Injury in Pakistan: A Retrospective Study

Abstract: Background Spinal cord injury has not received robust attention in Pakistan. The only time when the topic was highlighted was earthquake 2005 which struck the northern region of the country. More than 120?000 people lost their lives and a big number of survivors sustained injury to spinal cord. Study Design This was a retrospective trial where data from one of the oldest paraplegic centre was retrieved and analysed. Objectives The objective of this study was to report epidemiology of spinal cord injury in ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…According to Darain H, et al [70], one of their retrospective study in Pakistan from 2011 to 2016 concluded that male subjects are prone to at least 3 times higher than the female population and 90%) of the subjects were paraplegics. The majority of the illiterate class are more affected and most of the subjects are labors (21.4%) and in the female population majority of affected subjects are housewives (21.3%), and fall from height (30.4%), RTA (25.5%) and firearm injury (21.1%) are major cause of injury.…”
Section: Worldwide Epidemiological Datamentioning
confidence: 99%
“…According to Darain H, et al [70], one of their retrospective study in Pakistan from 2011 to 2016 concluded that male subjects are prone to at least 3 times higher than the female population and 90%) of the subjects were paraplegics. The majority of the illiterate class are more affected and most of the subjects are labors (21.4%) and in the female population majority of affected subjects are housewives (21.3%), and fall from height (30.4%), RTA (25.5%) and firearm injury (21.1%) are major cause of injury.…”
Section: Worldwide Epidemiological Datamentioning
confidence: 99%
“…The incidence of SCI varies widely, with developed nations reporting rates between 13.1 and 163.4 per million, whereas developing countries face incidences ranging from 13 to 210 per million (1)(2)(3). Data from Pakistan reveals a distribution wherein 10% of SCI cases result in tetraplegia and 90% in paraplegia, predominantly affecting males (4). The prospects for recovery diminish significantly after the initial three months post-injury, during which patients may develop secondary complications such as cardiovascular issues, pressure ulcers, chronic pain, respiratory complications, contractures, infections, and spasticity (5).…”
Section: Introductionmentioning
confidence: 99%
“…However, in countries like Pakistan, where resources are limited and no national registry for spinal injuries exists, the exact prevalence remains unknown. Estimates suggest that 90% of SCI individuals in Pakistan are paraplegics and the majority are male (5), highlighting an alarming prevalence in low-income countries, affecting around 207.9 million individuals (6).…”
Section: Introductionmentioning
confidence: 99%